(untitled) (Bangladesh Journal of Microbiology, 2021)
Fourteen multi drug resistant Staphylococcus aureus isolates from surgical site infection were analyzed for their antibiotic sensitivity and the presence of nine virulence genes. The isolates showed a high resistance pattern, all being resistant to methicillin, oxacillin, azithromycin, ceftazidime and amoxyclav. Seven of the isolates were sensitive to linezolid; three were sensitive to trimethoprim: sulfamethoxazol and another three were sensitive to ciprofloxacin. Ceftriaxone, gentamicin and amikacin were the drugs of choice as nine (64.3%) isolates were sensitive to ceftriaxone, eleven (78.6%) were sensitive to gentamicin and another eleven (78.6%) to amikacin. The present study focused to identify nine important virulence genes including intrinsic methicillin resistance gene mecA, methicillin resistance assisting gene femA, toxic shock syndrome toxin gene tst, exfoliative toxin A and B genes, eta and etb, Panton Valentine leukocidin gene LukS/F-PVL, along with three enterotoxin genes sec, sed and see. According to the presence of mecA gene and antibiotic resistance profile, two isolates were identified as methicillin resistant Staphylococcus aureus. However, another isolate, despite harbouring both mecA and femA genes, was sensitive to ceftriaxone which excluded it from being considered as an MRSA. Thus, the ratio of MRSA can be considered to be quite high (2/14) among the strains. Interestingly, most of the isolates (10/14) harboured femA gene, the majority of which were mecA negative with an MSSA type antibiotic profile. Although considered as a marker for community acquired MRSA, LukS/F-PV was found in half of these nosocomial isolates. Five, four and two of the isolates harboured etb, tst and sec gene, respectively. However, all the isolates were negative for eta, sed and see genes. Two isolates showed the co-existance of “femA, LukS/F-PV, etb, and tst” genes. Another two virulence gene patterns observed were “femA, mecA, tst, sec” and “femA, LukS/F-PV, etb”. The presence of several virulence genes can be correlated to the highly pathogenic nature of the isolates. Bangladesh J Microbiol, Volume 38, Number 1, June 2021, pp 21-26